Midbrain mutiny : the picoeconomics and neuroeconomics of disordered gambling : economic theory and cognitive science - Ross, Don, 1962- (Bradford book., 2008)
An analysis of how economic theories can be used to understand disordered and pathological gambling that calls on empirical evidence about behavior and the brain and argues that addictive gambling is the basic form of all addiction.